Modal approach to the controllability problem of distributed parameter systems - Zuyev, A.L. (Труды Института прикладной математики и механики, 2010)
This paper is devoted to the analysis of the controllability for a class of linear control systems in a Hilbert space. It is proposed to use the minimum energy control of a reduced lumped parameter system for solving the infinite dimensional steering problem approximately. Sufficient conditions of the approximate controllability are formulated for a modal representation of a flexible structure with small dissipation.